Hubungvan Pengetahuan Dan Dukungan Keluarga Dengan Minat Vaksinasi MR Di Wilayah Kerja Puskesmas Maros Baru Kabupaten Maros - Alfiah Alfiah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Introduction Measles and Rubella are infectious diseases through the respiratory tract with symptoms of high fever, reddish patches on the skin (rash). Analytical descriptive research method with a cross sectional study approach, which was conducted on January 14-31 2019 with a sample of 98 people, Knowledge Results This is related to maternal interest in giving MR vaccination, because respondents with good knowledge are more likely to be interested in giving MR immunization to children and family support is related to mother's interest in giving MR vaccination, because respondents with good knowledge are more likely to be interested in giving MR immunization to children. Conclusion There is a relationship between knowledge and family support with the interest in MR vaccination in the Maros Baru District Health Center Work Area. Maros.